2018
DOI: 10.31729/jnma.3640
|View full text |Cite
|
Sign up to set email alerts
|

Predisposing Factors and Outcome of Malpresentations in an Institute

Abstract: Introduction: This study was done to find out the incidence of malpresentation among all deliveries with various types of Malpresentations, its mode of delivery , maternal and fetal predisposing factors with outcome. Methods: This was a cross sectional descriptive study done at KIST Medical College and Teaching Hospital. Review cases of women admitted in labor after 22 weeks with malpresentation was done. Maternal/fetal predisposing factors were recorded. Results: Total delivery in study period was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 9 publications
1
4
0
Order By: Relevance
“…This is in line with the findings of a study done in Jimma Zone, Southwest Ethiopia (33) and Gamo Gofa, Ethiopia (26). This may be the case because malpresentation during pregnancy and labor increases the risk of birth hypoxia, birth trauma, and other complications and leads to obstructed and prolonged labor, which can result in neonatal morbidity and mortality (34).…”
Section: Discussionsupporting
confidence: 88%
“…This is in line with the findings of a study done in Jimma Zone, Southwest Ethiopia (33) and Gamo Gofa, Ethiopia (26). This may be the case because malpresentation during pregnancy and labor increases the risk of birth hypoxia, birth trauma, and other complications and leads to obstructed and prolonged labor, which can result in neonatal morbidity and mortality (34).…”
Section: Discussionsupporting
confidence: 88%
“…Similarly, the study conducted in Gamo Gofa, Ethiopia, found non-vertex fetal presentation was the determinant factor of NNM [ 23 ]. This might be since malpresentation during pregnancy and labor has a high risk of birth asphyxia, birth trauma, and other complications and also lead to obstructed and prolonged labor which can result in different complications to the newborn [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…malpresentation during pregnancy and labor has a high risk of birth asphyxia, birth trauma, and other complications and also lead to obstructed and prolonged labor which can result in different complications to the newborn [30]. Obstetric complications during labor and delivery were also showed a significant association with NNM.…”
Section: Plos Onementioning
confidence: 96%
“…Those studies found that neonates who had a non-vertex presentation were more likely to become near miss as compared to vertex presentation. This might be due to a high risk of birth asphyxia, trauma, and other complications caused by malpresentation during pregnancy ( 45 ). Malpresentation may lead to obstructed and prolonged labor, which can result in NNM through different complications to the newborn ( 45 ).…”
Section: Discussionmentioning
confidence: 99%
“…This might be due to a high risk of birth asphyxia, trauma, and other complications caused by malpresentation during pregnancy ( 45 ). Malpresentation may lead to obstructed and prolonged labor, which can result in NNM through different complications to the newborn ( 45 ).…”
Section: Discussionmentioning
confidence: 99%